Predicting socially anxious group membership using reinforcement sensitivity theory. (November 2015) - Kramer, Sam; Rodriguez, Benjamin F.; Kertz, Sarah J.
Abstract: The present study examined the role of revised reinforcement sensitivity theory (r-RST; Gray & McNaughton, 2000) in discriminating individuals with high and low levels of social anxiety. Participants were solicited online via Amazon's MTurk and completed measures of social anxiety and reinforcement sensitivity theory. Participants were divided into low versus high social anxiety groups based upon recommended cut off scores. A logistic regression analysis using the r-RST subsystems as predictors was able to successfully classify 88.3% of participants into social anxiety groups. More specifically, the Freeze component of the Fight–Flight–Freeze system and the behavior approach system both emerged as significant predictors of group membership. Implications of these results for the understanding of social anxiety in the context of revised reinforcement sensitivity theory are discussed. Highlights: Support for low BAS as a vulnerability for high levels of social anxiety The logistic regression using r-RST predictors correctly classified 88.3% of cases. Only BAS and Freeze variables emerged as significant predictors.